Student teachers’ level of reflection during teacher clinical experience: A case study in a Malaysian university - Min, Wong Yeou; Mansor, Rosnidar; Samsudin, Syakirah (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2016)
This study investigated student teachers’ (ST) level of reflection during teacher clinical experience (TCE). It sought to analyse the level of reflection among STs from a Malaysian university in the current practice of reflective writing and after given exposure to the critical reflection manual (CRM) during TCE. This study used Van Manen’s (1977) three-stage model (technical, practical and critical) to determine the level of reflection based on STs’ self-reflection notes in their daily lesson plan books (for the current practice of reflective writing) and weekly reflective journal writings (for STs who were given exposure to the CRM). The participants consisted of seven STs who were undergoing TCE from February to June 2014 (for the current practice) and eleven STs who were undergoing TCE from July to October 2015 (for those given exposure to the CRM). Each participant’s level of reflection was analysed based on Van Manen’s (1977) categorisation of levels of reflection. Results of the analyses showed that STs were barely reflective, demonstrating very low level of reflection for the current practice of reflective writing while STs exhibited practical and critical levels of reflection after given exposure to the CRM. Interpretations of the results are presented and recommendations are discussed within the context of the study.